The use of acetic acid bacteria isolated from palm vinegar to reduce the growth of Escherichia coli in white rats (Rattus norvegicus) - Rastina Rastina; Azhari Azhari; Andi Novita; Ismail Ismail; Darmawi Darmawi; Sri Wahyuni; Denny I. Hasan; Alfia Hidayatun; Marsya F. Fadila (Fakultas Peternakan Universitas Papua, 2026)
Acetic acid bacteria (AAB) have the potential to become the next generation of probiotics due to their ability to survive in acidic pH conditions, high temperatures, and exposure to bile acids. In addition, acetic acid bacteria are also known to have natural antimicrobial effects that can inhibit the growth of pathogenic bacteria such as Escherichia coli. This study was conducted to examine the effectiveness of acetic acid bacteria isolate cuka aren as a probiotic candidate in inhibiting the growth of Escherichia coli in white rats (Rattus norvegicus). This study used 24 male Wistar rats divided into four treatment groups, namely (K1) negative control, (K2) positive control, (P1) acetic acid bacteria 1.5 x 108 CFU/ml + pathogenic E. coli 1.5 x 108 CFU/ml, and (P2) acetic acid bacteria 6.0 x 108 CFU/ml + pathogenic E. coli 1.5 x 108 CFU/ml. Acetic acid bacteria were administered orally via a gastric tube on days 1 to 21. Pathogenic E. coli infection was performed orally using a gastric tube on days 8 to 14. Sampling of rat cecal digesta was performed on day 22, and the number of E. coli colonies was counted on Eosin Methylene Blue Agar (EMBA) medium and acetic acid bacteria on Pepton Yeast Glucose Agar (PYGA) medium using the Total Plate Count (TPC) method. The data obtained were analyzed using the Kruskal Wallis statistical test and followed by the Mann-Whitney test. Based on the results of the study, acetic acid bacteria isolated from palm vinegar were proven to be able to reduce the growth of E. coli in white mice, with group P2 being the most effective treatment because it showed a decrease in the number of E. coli and the highest growth in the number of acetic acid bacteria colonies.